Government confronts culture : the struggle for democracy in Southern Africa - Fuller, Bruce (States and societies ;, 1999)
Transitional societies -- struggling to build democratic institutions and new political traditions -- are faced with a painful dilemma. How can Government become strong and effective, building a common good that unites disparate ethnic and class groups, while simultaneously nurturing democratic social rules at the grassroots? Professor Fuller brings this issue to light in the contentious, multicultural setting of Southern Africa. Post-apartheid states, like South Africa and Namibia, are pushing hard to raise school quality, reduce family poverty, and equalize gender relations inside villages a.